Competency measurements: testing convergent validity for two measures - Cowin, L.; Hengstberger-Sims, C.; Eagar, S.; Gregory, L.; Andrew, S.; Rolley, John Xavier (Blackwell Publishing Ltd, 2008)
This paper is a report of a study to investigate whether the Australian National Competency Standards for Registered Nurses demonstrate correlations with the Finnish Nurse Competency Scale. Competency assessment has become popular as a key regulatory requirement and performance indicator. The term competency, however, does not have a globally accepted definition and this has the potential to create controversy, ambiguity and confusion. Variations in meaning and definitions adopted in workplaces and education settings will affect the interpretaion of research findings and have implications for the nursing profession.Correlational analysis of self-assessed levels of competence revealed a relationship between the Australian National Competency Standards (ANCI) and the Nurse Competency Scale (NCS). The correlational relation between ANCI domains and NCS factors suggest that these scales are indeed used to measure related dimensions. A statistically significant relationship (r = 0.75) was found between the two competency measures.Although the finding of convergent validity is insufficient to establish construct validity for competency as used in both measures in this study, it is an important step towards this goal. Future studies on relationship between competencies must take into account the validity and reliability of the tools.